Evaluating the impact of metabolic and cognitive stress on ghrelin and nesfatin‐1 hormones in patients with diabetes and diabetic depression - Algul, Sermin; Ozcelik, Oguz (Wiley, 2024)
AbstractNesfatin‐1 and ghrelin, initially recognised as hormones involved in regulating energy, have emerged as crucial players with vital functions in various human body systems. In this study, we conducted a comparative assessment of nesfatin‐1 and ghrelin responses in individuals experiencing metabolic stress due to diabetes, those with depressive diabetes characterised by both metabolic and mental stress, and healthy controls. We collected blood samples from a total of 90 participants, consisting of 30 people with type II diabetes mellitus (DM), 30 people with type II DM and major depressive disorders, and 30 healthy individuals. Diabetes was diagnosed based on glycated haemoglobin (HbA1c) levels, while depression was assessed using DSM‐V criteria. Insulin resistance (HOMA‐IR) was calculated, and serum ghrelin and nesfatin‐1 levels were measured using ELISA kits. We observed statistically significant decreases in nesfatin‐1 and ghrelin levels in the diabetic group (p < 0.0001). However, in the depressive diabetic group, nesfatin‐1 levels increased significantly, while ghrelin levels decreased further. The nesfatin‐1 to ghrelin ratio decreased in the diabetic group but increased significantly in the depressive diabetic group (p < 0.0001). Nesfatin‐1 and ghrelin hormones exhibit parallel impacts in response to metabolic stress, but nesfatin‐1 demonstrates contrasting actions compared to ghrelin when mental stress is added to metabolic stress. The findings of this study suggest that nesfatin‐1 and ghrelin hormones may play active roles as protective, prognostic, and even etiological factors in various stress situations, particularly those involving mental stress, in addition to their known functions in regulating energy.
Keywords: Male; Adult; Depressive Disorder, Major; Calcium-Binding Proteins; Nerve Tissue Proteins; Middle Aged; Ghrelin; DNA-Binding Proteins; Diabetes Mellitus, Type 2; Stress, Physiological; Humans; Nucleobindins; Female; Stress, Psychological; 3. Good health